A Small Key for a Heavy Door: Genetic Therapies for the Treatment of Hemoglobinopathies - Zittersteijn, Hidde A.; Harteveld, Cornelis L.; Klaver-Flores, Stefanie; Lankester, Arjan C.; Hoeben, Rob C.; Staal, Frank J. T.; Gonçalves, Manuel A. F. V. (Frontiers in Genome Editing, 2021)
Throughout the past decades, the search for a treatment for severe hemoglobinopathies has gained increased interest within the scientific community. The discovery that ɣ-globin expression from intact HBG alleles complements defective HBB alleles underlying β-thalassemia and sickle cell disease, has provided a promising opening for research directed at relieving ɣ-globin repression mechanisms and, thereby, improve clinical outcomes for patients. Various gene editing strategies aim to reverse the fetal-to-adult hemoglobin switch to up-regulate ɣ-globin expression through disabling either HBG repressor genes or repressor binding sites in the HBG promoter region. In addition to these HBB mutation-independent strategies involving fetal hemoglobin (HbF) synthesis de-repression, the expanding genome editing toolkit is providing increased accuracy to HBB mutation-specific strategies encompassing adult hemoglobin (HbA) restoration for a personalized treatment of hemoglobinopathies. Moreover, besides genome editing, more conventional gene addition strategies continue under investigation to restore HbA expression. Together, this research makes hemoglobinopathies a fertile ground for testing various innovative genetic therapies with high translational potential. Indeed, the progressive understanding of the molecular clockwork underlying the hemoglobin switch together with the ongoing optimization of genome editing tools heightens the prospect for the development of effective and safe treatments for hemoglobinopathies. In this context, clinical genetics plays an equally crucial role by shedding light on the complexity of the disease and the role of ameliorating genetic modifiers. Here, we cover the most recent insights on the molecular mechanisms underlying hemoglobin biology and hemoglobinopathies while providing an overview of state-of-the-art gene editing platforms. Additionally, current genetic therapies under development, are equally discussed.